Antidiabetic and antioxidant activity of Annona squamosa extract in streptozotocin-induced diabetic rats - Kaleem, Mohammed; Asif, Mohd S.; Ahmed, Qamar Uddin; Bano, Bilqees (Singapore Medical Association, 2006)
Introduction: The aim of the study is to analyse the antioxidant effect of oral administration of aqueous extract of Annona squamosa (A. squamosa) leaf on blood glucose, haemoglobin, glycosylated haemoglobin, plasma insulin, antioxidant enzymes and lipid peroxidation in liver and kidney to streptozotocin (STZ)-induced diabetic rats. Methods: Aqueous extract of A. squamosa on blood glucose, haemoglobin, glycosylated haemoglobin, plasma insulin, serum lipid and the levels of lipid peroxides and antioxidant enzymes, such as catalase, superoxide dismutase, glutathione peroxidase and reduced glutathione, were examined in the liver and kidney tissues of control and experimental groups. Results: Oral administration of A. squamosa aqueous extract to diabetic rats for 30 days significantly reduced the levels of blood glucose, lipids and lipid peroxidation, but increased the activities of plasma insulin and antioxidant enzymes, like catalase, superoxide dismutase, reduced glutathione and glutathione peroxidase. Conclusion: The A. squamosa aqueous extract supplementation is useful in controlling the blood glucose level, improves the plasma insulin, lipid metabolism and is beneficial in preventing diabetic complications from lipid peroxidation and antioxidant systems in experimental diabetic rats; therefore, it could be useful for prevention or early treatment of diabetes mellitus.